Statistical dependence of average intercore crosstalk on random loss in long-haul uncoupled MCF links - Rebola, J. L.; Cartaxo, A. V. T. (2023 IEEE Photonics Conference (IPC), 2023)
Random core dependent loss (CDL) in long-haul uncoupled multicore fiber links is shown by simulation to lead to gaussian-distributed average crosstalk power. Due to CDL randomness, the excess of average crosstalk power relative to its mean is below 0.2 dB in 2000 km-long links.